MIMO Radar Transmit Beampattern Design for DOA Estimation with Sidelobe Suppression - Yuxiang Li; Shuainan Gu; Nae Zheng (International Journal of Antennas and Propagation)
We address the problem of transmit beamspace design for multiple-input multiple-output (MIMO) radar with colocated antennas in direction-of-arrival (DOA) estimation application. Three transmit beampattern sidelobe suppression strategies for designing the transmit beamspace matrix are introduced. The design of transmit beamspace matrix is based on minimizing the difference between a desired transmit beampattern and the actual one while keeping the sidelobe levels under control. Uniform elemental power distribution across the transmit antenna is guaranteed; at the same time, signal rotational invariance property is considered, which enables search-free based DOA estimation algorithms to be utilized at the receiver. The proposed optimization problems are nonconvex and are solved by using semidefinite programming relaxation technique. Moreover, the DOA estimation Cramer-Rao bound with transmit beamspace matrix is discussed. Simulation results show the superiority of the proposed techniques over the existing methods.